خريطة الدعوة في ولاية جوهر:منهجها وتطبيقها في مناطق سكودي,فاسير كودعووجوهر بهارو - Muhammad Ismail Bin Mushtari
This study aims at looking into the mapping of dakwah (invitations to Islam), its methodology and applications within the district of Johor Bahru, Johor. This dakwah mapping will look at the aspects of populations, geography, facilities, background of the society, social status, costing, duration as well as those involved in the dakwah activity. A few techniques were employed to collect the data for the study i.e, questionnaire and observation, interviews and observations at the study locations. In all, 531 respondents responded to 135 questions in the questionnaire. SPSS version 14.0 was used to analysis the data to find frequency, percentages and min value. The value of reliability was a =0.803. The findings of the study show that there were several methodologies which identified as active at four locations of the study such as seven programs related to al- Quran, fifteen programs of lectures and talks, six related zakat (paying tribute), fast and pilgrimage, and thirteen society based programs. Other dakwah program received less participation such as eleven programs related to family issues, seven related to mosques and twenty five programs in the form of workshops, courses and seminar. The respondents from the four areas were very agreed that the preachers need to preach with wisdom so that the preaching would be more effective and the administration of the dakwah in their locations should be improved. The majority of the respondents believed that the dakwah approach which was carried out by the current organization ought to be improved in term of promotion, appearance and target friendly. They also have the opinion that there were not many programs especially for women, teenagers and children in their locations. The contribution of this study is as a platform to upgrade the quality of dakwah which is required from each governmental agency, NGOs and all those who are involved in dakwah in order to generate a reformation towards a more competent, comprehensive and flexible direction.